French intellectuals in the 20st century - Ferrari, Alain; Harari, Simone Hlaberstadt; Levy, Bernard-Henri; Films for the Humanities (Firm) (Princeton, NJ: Films for the Humanities, 1993)
Follows French intellectualism from its initial appearances in the 20th century with Zola and Proust, through both world wars, to Satre and the present
part 1. Great expectations - part 2. Days of contempt - part 3. Lost illusions - part 4. The demise of the prophets
Director of photography, Daniel Barrau, Jean-Marie Lequertier, Alexander Valenti ; editor, Maurice Rose ; music, Denis Barbier
Keywords: French literature -- 20th century; Philosophy, French -- 20th century; France -- Intellectual life -- 20th century